Do Personality and Organizational Politics Predict Workplace Victimization? A Study among Ghanaian Employees. - Amponsah-Tawiah, K.; Annor, F. (ELSEVIER, 2017)
Background Workplace victimization is considered a major social stressor with significant implications for the wellbeing of employees and organizations. The aim of this study was to examine the influences of employees' personality traits and organizational politics on workplace victimization among Ghanaian employees. Methods Using a cross-sectional design, data were collected from 631 employees selected from diverse occupations through convenience sampling. Data collection tools were standardized questionnaires that measured experiences of negative acts at work (victimization), the Big Five personality traits, and organizational politics. Results The results from hierarchical multiple regression analysis showed that among the personality traits neuroticism and conscientiousness had significant, albeit weak relationships with victimization. Organizational politics had a significant positive relationship with workplace victimization beyond employees' personality. Conclusion The study demonstrates that compared with personal characteristics such as personality traits, work environment factors such as organizational politics have a stronger influence on the occurrence of workplace victimization
Journal Article
Keywords: Ghana; organizational politics; personality; workplace victimization